Automating the analysis of NCL documents with a model-driven approach - Santos, Joel André Ferreira dos; Braga, Christiano; Muchaluat-Saade, Débora C. Muchaluat (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
This paper presents a model-driven approach for the analysis of NCL documents. Structural and behavioral properties of NCL documents are verified guaranteeing its well-formedness and conformance with respect to the NCL language semantics. Document structural properties are verified using invariant validation and document behavioral properties are verified through model checking. The model-driven approach proposed is based on a formal and simplified model for representing the NCL document presentation behavior called Simple Hypermedia Model (SHM), used for the verification of document properties. In addition, this paper presents a prototype implementation of the proposed approach.